The Influences of Open Access of Online Health Information on Patient Compliance to Professional Healthcare Providers Prescription in Kasangati Town Council, Wakiso District Uganda - Nakitto, Martha Hope; Mirembe, Drake Patrick; Waako, Christopher; Lubega, Jude; Kibukamusoke, Martha; Nambogo, Fiona (Advances in Social Sciences Research Journal, 2022)
Globally the health sector has witnessed disruptive transformation of how information is; generated, analyzed and shared using Information Communication Technologies (ICT). There is limited understanding on how patient’s access of online health information influences their desire to seek professional healthcare services or their adherence to professional healthcare service providers prescription/advise. Thus, the aim of this study was to investigate the influence that online health information has on patients’ compliance to professional healthcare service provider’s case management plans in Kasangati Town Council, Wakiso District, Uganda. Results show that, availability of internet, accessibility and availability of information and desire to gain deeper understanding are some of key factors that influence patients to access online health information. The study further revealed that access to online health information reinforces patient desired to seek professional care services and adhere to a case management plan provided by the health workers in addition to improving patient awareness and participation in management of their health.